The Efficacy of Instagram Reels on Speaking Learning at Senior High School - Dinda Tri Widiyanti; Dian Fadhilawati (Pusat riset dan Inovasi Nasional, 2024)
Speaking ability is a key aspect emphasized in the language learning process. Having the ability to speak English is very important for students, as this allows them to express their skills in the language. This research aims to determine the efficacy of the learning media application Instagram reels to improve students' speaking learning outcomes in report texts at SMAN 1 Sutojayan, especially in class X-3. The research involved 37 students in class X-3 using a quantitative approach with a one-group pre-test and post-test design. The research results show that the alternative research hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This research provides an understanding of the importance of improving students' speaking skills by developing more efficient learning strategies. The results of this research can provide a valuable contribution to efforts to improve the quality of education at SMAN 1 Sutojayan and similar educational institutions. Additionally, future researchers are advised to investigate the long-term impact of utilizing Instagram Reels or similar interactive tools on students' overall academic achievement and morale.